The effectiveness of ultrasound guided hydrodistension and physiotherapy in the treatment of frozen shoulder/adhesive capsulitis in primary care: a single centre service evaluation. Issue 4 (October 2017) - Bryant, Michael; Gough, Andrew; Selfe, James; Richards, Jim; Burgess, Elizabeth
Background: Evidence for optimal non-operative treatment of frozen shoulder is lacking. The present study aimed to evaluate a treatment strategy for stage II to III frozen shoulder provided by the current primary care musculoskeletal service. Methods: General practioner referrals of shoulder pain to the musculoskeletal service diagnosed with stage II to III frozen shoulder and who opted for a treatment strategy of hydrodistension and guided physiotherapy exercise programme over a 12-month period were evaluated for 6 months. Thirty-three patients were diagnosed with stage II to III frozen shoulder by specialist physiotherapists and opted for the treatment strategy. Outcome measures included Shoulder Pain Disability Index (SPADI) and Shortened Disabilities of the Arm, Shoulder and Hand (QuickDASH), pain score and range of movement. Data were collected at baseline, as well as at 6 weeks, 12 weeks and 6 months. Results: All patients significantly improved in shoulder symptoms on the SPADI and QuickDASH scores ( p  < 0.001). Pain scores and range of shoulder movement flexion, abduction, external rotation showed significant improvement at all time points ( p  < 0.001). Conclusions: This service evaluation demonstrates that management of frozen shoulder stage II to III, as conducted by physiotherapists in a primary care setting utilizing hydrodistension and a guided exercise programme, represents an effective non-operative treatment strategy.